Challenges in schistosomiasis control in Sergipe, Brazil: from 2013 to 2018 (Research, Society and Development, 2020)
This study aimed to analyze the performance of the Schistosomiasis Epidemiological Surveillance System in Sergipe, Brazil. This study used a mixed methodology, with a quantitative approach and the application of semi-structured interviews, directed to professionals of Health Surveillance and Primary Care in seven regional health departments headquarters in Sergipe, as well as information obtained in Sistema de Informação do Programa de Controle da Esquistossomose (SISPCE), Sistema de Informação sobre Mortalidade (SIM) and Sistema de Informação de Agravos de Notificação (SINAN). Interviews were applied from March to October 2018 and secondary data obtained in the information systems corresponded to the period between 2013 and 2018, when structure and process indicators were compared with result indicators. The main critical point was the lack of implementation of the Schistosomiasis Control Program (PCE) in the entire endemic area, lack of interaction between Epidemiological Surveillance and Primary Care, deficiencies in the management and execution of field actions. Failures in the implantation in the PCE, in the structure and process of the Surveillance System, in addition to the need for greater integration between the professionals of the Epidemiological Surveillance and other health sectors, negatively influence the results of the PCE, and may have similar causes and results in the others endemics of the state.